The Others Are Too Loud! Children’s Experiences and Thoughts Related to Voice, Noise, and Communication in Nordic Preschools - McAllister, Anita; Rantala, Leena; Jónsdóttir, Valdís Ingibjörg (Frontiers in Psychology, 2019)
Background: High noise levels affect hearing, voice use and communication. Several studies have reported high noise levels in preschools and impaired voice quality in children. Noise and poor listening conditions impair speech comprehension in children more than in adults and even more for children with hearing or language impairment, attention deficits or another first language. The aim of this study was to explore how children in Finland, Sweden and Iceland describe the preschool environment in relation to noise, voice and verbal communication; what were their experiences, knowledge and ideas in relation to voice, noise and communication. Children’s awareness of effects of noise, reactions and coping strategies were also studied. In addition, country and gender differences were analyzed. Methods: Eighteen Icelandic, 14 Finnish and 16 Swedish children were interviewed using a common interview-guide. Swedish and Finnish children were interviewed in focus groups and Icelandic children individually. All interviews were transcribed verbatim and analyzed thematically by the native speaker. The interviews were translated to English to be re-analyzed for inter-judge reliability of identified themes. Inter-judge reliability was calculated using percentage absolute agreement. Results: The interviews resulted in 1052 utterances, 471 from focus groups and 581 from individual interviews. Three themes were identified, Experiences, Environment and Strategies with two to three subcategories. Inter-judge agreement for the themes was excellent, 92 to 98 %. Experiences occurred in 55% of the utterances. The subcategories were bodily and emotional experiences and experiences of hearing and being heard. Environment occurred in 20% of the utterances, with subcategories indoor vs outdoor and noise. Strategies was found in 15%, with subcategories games and problem oriented actions. The only significant difference between the countries was for the theme Strategies where the Swedish children produced more utterances than the Finnish. No gender differences were found. Conclusion: Children are aware of high noise levels and mainly blame other children for making noise and shouting. They describe reactions and strategies related to noise like impaired communication and effects on hearing but are less aware of effects on voice. Expressed thoughts were similar across countries. No gender differences were found.